Self-selection at the candidate level of simultaneous interpreting - Kapranov, Oleksandr (Lesya Ukrainka Eastern European National University, 2015)
Abstract. This article aims at outlining the role of self-selection in the decision by the potential students of simultaneous interpreting, i.e. interpreter candidates, to apply for a university programme in simultaneous interpreting. The role of self-selection is investigated by means of a psycholinguistic experiment involving the potential students’ written reflections on the topic ‘Why I Chose to Apply for a University Programme in Simultaneous Interpreting’. The experiment is conducted with six interpreter candidates (further referred to as ‘participants’) who want to apply for university translation and interpreting programmes at Stockholm University (Sweden), Brussels Free University (Belgium) and University of Seville (Spain) respectively. The study’s specific objective is to identify main categories involved in the participants’ self-selection of the university programme in simultaneous interpreting. The participants are instructed to write a 500 words essay on the topic ‘Why I Chose to Apply for a University Programme in Simultaneous Interpreting’. The corpus of the participants’ essays is subsequently tagged in computer program CLAN in order to facilitate the identification of the self-selection categories. Data analysis reveals that the most frequent categories involved in self-selection are ‘Interest’, ‘Communication with other people’, ‘Another identity’, ‘Novelty’ and ‘Interpreting as a natural choice’ respectively.
Keywords: simultaneous interpreting, self-selection, psycholinguistics, interpreter candidates, application for a university course in simultaneous interpreting